Pelayanan Administrasi Pertanahan Di Kecamatan Marpoyan Damai Kota Pekanbaru - Alma Apriliya Regita; Abdul Sadad (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
The application of the Land Information System (SIPTANAH) in Marpoyan Damai District is a form of innovation from Mr. Fiora as the sub-district head in Marpoyan Damai District for the 2016-2019 term. This aims to facilitate urban villages that provide direct services to the community in land administration management services through SIPTANAH. This study aims to determine how the application of land administration management services through SIPTANAH in Marpoyan Damai District and the inhibiting factors of application that make land administration management through SIPTANAH no longer used in mid-2019. The theory used in this study is the theory of Taliziduhu Ndraha (2001: 67) which suggests that there are 4 (four) indicators in determining the quality of service, namely: Speed, Accuracy, Easiness, and Justice. This research uses qualitative research with a case study approach and the required data both primary and secondary are obtained from observation, interview and documentation techniques for further analysis using the interactive model of Miles and Huberman. The results of this study indicate that, the application of land administration services through SIPTANAH is quite optimal, but there are still several indicators that must be added, one of which is the human resources for operators who take care of land administration services through SIPTANAH at both the District and Kelurahan levels. And the inhibiting factors for the application of land administration services through SIPTANAH in Marpoyan Damai District are the lack of cooperation between the sub-district government and the village government, and outreach to the kelurahan.